2008
DOI: 10.1007/s10350-008-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stomas for Recurrent Life-Threatening Gastrointestinal Bleeding: Report of a Case

Abstract: Acute lower gastrointestinal hemorrhage is an uncommon and severe symptom. The overall mortality rate ranges from 5 to 12 percent and can approach 40 percent for persistent or recurring bleedings. We report a case of a patient with severe recurrent lower bleeding in whom, despite several repeated explorations and a blind subtotal colectomy, no lesion could be found. Multiple (n = 4) leveled stomas of the small bowel with succus entericus reinfusion were required to localize and treat the cause of the bleeding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…11 However, these complications appeared to represent unmasking of existing pathologies or progression of underlying pathology rather than being complications of CR per se, as these were patients excluded from the reinfused group. Specific mention of no adverse events (AEs) related to reinfusion were reported in 6 articles, 15,18,21,27,37,38 whereas 11 other studies did not report whether any AEs occurred. 13,19,28,[30][31][32][33][34][35]39,40 No studies reported any serious AEs or mortality directly associated with CR.…”
Section: Adverse Events and Mortalitymentioning
confidence: 99%
“…11 However, these complications appeared to represent unmasking of existing pathologies or progression of underlying pathology rather than being complications of CR per se, as these were patients excluded from the reinfused group. Specific mention of no adverse events (AEs) related to reinfusion were reported in 6 articles, 15,18,21,27,37,38 whereas 11 other studies did not report whether any AEs occurred. 13,19,28,[30][31][32][33][34][35]39,40 No studies reported any serious AEs or mortality directly associated with CR.…”
Section: Adverse Events and Mortalitymentioning
confidence: 99%